2019
DOI: 10.1016/j.eururo.2018.09.041
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Association between Physical Activity and Risk of Prostate Cancer Defined by Clinical Features and TMPRSS2:ERG

Abstract: certifies that all conflicts of interest, including specific financial interests and relationships and affiliations relevant to the subject matter or materials discussed in the manuscript (eg, employment/affiliation, grants or funding, consultancies, honoraria, stock ownership or options, expert testimony, royalties, or patents filed, received, or pending), are the following: None.Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Lifestyle may also play a role in the development of PCa defined by TMPRSS2:ERG . For example, lycopene consumption from tomato products has been shown to be inversely associated with ERG‐positive but not ERG‐negative disease, and two studies have shown obesity to be associated with a reduced risk of developing TMPRSS2:ERG ‐positive PCa .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lifestyle may also play a role in the development of PCa defined by TMPRSS2:ERG . For example, lycopene consumption from tomato products has been shown to be inversely associated with ERG‐positive but not ERG‐negative disease, and two studies have shown obesity to be associated with a reduced risk of developing TMPRSS2:ERG ‐positive PCa .…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle may also play a role in the development of PCa defined by TMPRSS2:ERG. [11][12][13][14][15][16] For example, lycopene consumption from tomato products has been shown to be inversely associated with ERG-positive but not ERG-negative disease, 11 and two studies have shown obesity to be associated with a reduced risk of developing TMPRSS2:ERG-positive PCa. 12,13 Given that families often share lifestyle exposures, the association between a family history of PCa and molecular subtypes of PCa could operate through environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is sufficient evidence demonstrating the favourable effects of exercise on symptom control and quality of life (QOL) in prostate cancer, such as in countering the effects of androgen deprivation therapy [35,36,37]. Epidemiological studies have suggested that exercise may improve disease-specific and overall survival in prostate cancer [38,39]; however, this has yet to be demonstrated in a clinical population.…”
Section: When Exercise Is the Drug: Can Activity Levels Really Be mentioning
confidence: 99%